2014
DOI: 10.3389/fendo.2014.00146
|View full text |Cite
|
Sign up to set email alerts
|

An Evo-Devo Approach to Thyroid Hormones in Cerebral and Cerebellar Cortical Development: Etiological Implications for Autism

Abstract: The morphological alterations of cortical lamination observed in mouse models of developmental hypothyroidism prompted the recognition that these experimental changes resembled the brain lesions of children with autism; this led to recent studies showing that maternal thyroid hormone deficiency increases fourfold the risk of autism spectrum disorders (ASD), offering for the first time the possibility of prevention of some forms of ASD. For ethical reasons, the role of thyroid hormones on brain development is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 370 publications
(477 reference statements)
1
58
0
3
Order By: Relevance
“…Alternatively, increased CT in CH may have arisen from disturbances in eliminating transitory ipsi-and contra-lateral connections within the cortex because of the lengthened period of maturation from their hypothyroidism (24). In other words, cortical thickening may represent a more juvenile pattern of brain development than seen in TDC.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, increased CT in CH may have arisen from disturbances in eliminating transitory ipsi-and contra-lateral connections within the cortex because of the lengthened period of maturation from their hypothyroidism (24). In other words, cortical thickening may represent a more juvenile pattern of brain development than seen in TDC.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, embryonic day 0 (E0) is the day of conception; birth occurs at E21-E22, while fetal thyroid is functional at E17. [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Neurogenesis and migration in the rat occur over 10 days, between E11 and E21, and therefore a period of 3 days in rat brain development corresponds roughly to 37-38 days in humans (13).…”
Section: Animal Models Of Imhmentioning
confidence: 99%
“…Subsequent studies in the next two decades identified T 4 in coelomic fluid at 6 weeks gestation (7) and further described the details of TRs and deiodinase activity in early fetal brain (8,9,10). In more recent years, multiple TH responsive genes have been identified (11,12), including genes involved in differentiation, migration, myelination, axonal growth and synapse formation. Thyroid hormone is believed to play a key role in the processes of neuronal migration in the hippocampus and neocortex, development of cortical connections, cytoskeleton assembly, and neuronal development and maturation.…”
Section: Thyroid Hormone and Fetal Brain Developmentmentioning
confidence: 99%
“…Recent studies have shown cortical inhibition altered in hypothyroid rats (Navarro et al, 2015) and in NMDAr (N-methyl-Daspartate receptor) antagonist MK-801-treated mice (Gomes et al, 2014), both showing a reduction in the percentage of PPI. All these data strongly suggest that the analysis of the balance of excitatory to inhibitory inputs in the cerebral cortex is fundamental for the understanding of psychiatric disorders, most of them associated with developmental alterations during corticogenesis (Berbel et al, 2014;Volk and Lewis, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Cortical disinhibition is associated to preattentional deficits that are core symptoms of schizophrenia (Glausier et al, 2014;Lewis, 2014;Pezze et al, 2014;Volk and Lewis, 2014). However, recently altered GABAergic gene expression in ADHD children has also been reported (Wang et al, 2012), and alterations in PV-immunoreactive (PV-ir) neurons have been found in hypothyroid rats (Berbel et al, 1996), in humans suffering from epilepsy (DeFelipe, 2004), and in ASD patients (Berbel et al, 2014;Stoner et al, 2014). Recent studies have shown cortical inhibition altered in hypothyroid rats (Navarro et al, 2015) and in NMDAr (N-methyl-Daspartate receptor) antagonist MK-801-treated mice (Gomes et al, 2014), both showing a reduction in the percentage of PPI.…”
Section: Introductionmentioning
confidence: 99%